UMP and DOSM empower Statistical Communication - Nor Salwana, Mohammad Idris (2022)
PAYA Besar, 15 June 2022 - The Department of Statistics Malaysia (DOSM) in collaboration with the Centre for Artificial Intelligence and Data Science, Universiti Malaysia Pahang (UMP) organised a Statistics Forum in conjunction with Program Jelajah DUN with Public Higher Education Institutions (IPTA) in Astaka Hall, UMP Gambang Campus recently.